An overview on monkeypox virus: Pathogenesis, transmission, host interaction and therapeutics - Rampogu, Shailima; Kim, Yongseong; Kim, Seon-Won; Lee, Keun Woo (Frontiers in Cellular and Infection Microbiology, 2023)
Orthopoxvirus is one of the most notorious genus amongst the Poxviridae family. Monkeypox (MP) is a zoonotic disease that has been spreading throughout Africa. The spread is global, and incidence rates are increasing daily. The spread of the virus is rapid due to human-to-human and animals-to-human transmission. World Health Organization (WHO) has declared monkeypox virus (MPV) as a global health emergency. Since treatment options are limited, it is essential to know the modes of transmission and symptoms to stop disease spread. The information from host–virus interactions revealed significantly expressed genes that are important for the progression of the MP infection. In this review, we highlighted the MP virus structure, transmission modes, and available therapeutic options. Furthermore, this review provides insights for the scientific community to extend their research work in this field.